Sweetpotato breeding for northeastern Uganda: Farmer varieties, farmer-participatory selection, and stability of performance - Abidin, P.E. (Wageningen University & Research, 2004)
Between 1999 and 2001, the author conducted various studies, primarily in northeastern Uganda, aimed at rapidly assessing the potential of farmer varieties of sweetpotato (Ipomoea batatas) from northeastern Uganda in contributing to the varietal improvement programme in Uganda. These studies included: (i) collection of germplasm (farmer varieties) and farmer knowledge about varieties from five districts in northeastern Uganda; (ii) assessment of morphological diversity and duplication in the collected germplasm; (iii) farmer participatory on-station selection of promising varieties from the collected germplasm for on-farm and multi-locational testing; (iv) farmer-managed on-farm testing in Soroti District (northeastern Uganda) of selected farmer varieties, cultivars from the Ugandan breeding programme and local farmer varieties; (v) multi-locational testing and stability analysis of selected farmer varieties and officially released cultivars from the Ugandan breeding programme in multiple test environments (20 tests over three seasons). Additionally, the author presents results from a multi-national, multi-locational test of elite sweetpotato germplasm in eastern Africa used to study selection efficiency. During germplasm collections, a total of 206 accessions were collected, along with farmer knowledge about them, and of these 188 were classified as distinct accessions, exhibiting considerable morphological variation. Many accessions were collected from remote locations where sweetpotato is not a commercial crop, while relatively few accessions were collected from areas where the crop is important commercially. During the on-station assessment of the collected germplasm, 11 accessions were selected for further testing from a total of 160 accessions evaluated at two sites. Nine of the 11 accessions selected by farmers were common to both sites. Farmer selection criteria were verified, with a high weighting given to fresh storage root yield, storage root number and harvest index, in addition to root dry matter content and appearance. During on-farm trials over two years, the 11 farmer varieties were generally preferred over local varieties, and cultivars from the Ugandan breeding programme. During multi-locational trials, the 11 farmer varieties on average performed better with respect to broad adaptation, specific adaptation and yield stability, than the cultivars from the breeding programme. In addition, some of the farmer varieties showed specific adaptation to local environments. Results of the multi-national trial were analysed to generate recommendations for optimum selection efficiency, and indicated a two-step selection procedure with two locations and one replication at Selection Step 1 and five locations and two replications at Selection Step 2 (total test capacity of between 450 and 950 plots). During the farmer participatory phases of this research, farmers were highly competent in sweetpotato varietal selection and were aware of the genotype-by-environment interactions and biodiversity. Results illustrate the potential that farmer varieties can have in the improvement of sweetpotato in Uganda and other regions where high diversity of sweetpotato landraces exists, and allowed us to recommend an approach for the rapid and efficient selection of superior genotypes from local germplasm in East Africa.